Prevalence risk of sarcopenia in older Brazilian adults during the pandemic: A cross-sectional analysis of the Remobilize Study - Batista, Patricia Parreira (2023)
BACKGROUND: Social distancing has led to lifestyle changes among older adults during the coronavirus disease 2019 (COVID-19) pandemic. OBJECTIVES: This study aimed to estimate the prevalence risk of sarcopenia (RS) and investigate its associated factors during the COVID-19 pandemic in older Brazilian adults. DESIGN AND SETTING: Cross-sectional observational analysis of baseline data as part of the Remobilize Study. METHODS: Participants in the study were older adults (≥ 60 years), excluding those who were bedridden or institutionalized. The data collected consisted of answers about the RS (SARC-F), functional status, walking, sedentary behavior (SB), pain, comorbidity, and life space mobility. RESULTS: A total of 1,482 older adults (70 ± 8.14 years, 74% women) participated in the study, and an RS prevalence of 17.1% was found. (95% confidence interval [CI] 15.25–19.15%). The adjusted multivariate model showed a significant association between RS and functional limitation (odds ratio [OR]: 19.05; CI 13.00–28.32), comorbidity (OR: 5.11; CI 3.44–7.81), pain (OR: 4.56; CI 3.33–6.28), total walking (OR: 0.99; CI 0.99–1.00), SB of 8–10 hours (OR: 1.85; CI 1.15–2.93), and SB of > 10 hours (OR: 3.93; CI 2.48–6.22). RS was associated with mobility during the pandemic (OR: 0.97; CI 0.96–0.98). P < 0.05. CONCLUSIONS: During the pandemic, the prevalence of RS in older Brazilians was estimated at 17.1%. Moderate to severe functional limitation, comorbidities, presence of pain, walking, longer SB period, and reduced life space mobility significantly contributed to RS in older adults during the pandemic.